Impact of molecular genetic profle of meningiomas on the clinical course and recurrence using combined modality treatment - G. S. Sergeev; A. S. Gaytan; M. A. Travin; A. B. Ponomarev; M. A. Afonina; I. A. Savitskaya; F. Yakhya; A. L. Krivoshapkin (Сибирский онкологический журнал, 2024)
Introduction. Meningioma is one of the most common central nervous system tumors, accounting for 39.7 % of all primary brain tumors. The tumor originates from arachnoid meningothelial cells and is characterized by a wide range of histological types classified into 15 subtypes. The histological classification of meningiomas allows us to predict meningioma behavior and the risk of disease recurrence, as well as to define treatment strategies. However, clinical outcomes in histological subgroups of patients are often inconsistent with the histological grade of malignancy. Thus, a more reliable method is needed both to determine the histological subtype of the tumor and to predict the clinical course of the disease with the potential for targeted treatment.The purpose of the study was to summarize the available data on the effect of results of the genomic and proteomic tumor analysis on carcinogenesis with the relationship between the mutational changes and noninvasive diagnosis, treatment and the course of the disease.Material and Methods. Literature search was carried out in the PubMed, Elibrary system, publications were included mainly from 2010 to 2023. with the identification of articles by the keyword “genetic analysis of meningiomas” and synonyms. 550 articles were found, of which 55 were used to write a literature review.Conclusion. The study of the molecular genetic profile of meningiomas will improve the classification and establish a correlation with MRI data, the course of the disease and prognosis.